EVALUASI KAMPANYE PILKADA SERENTAK PADA MASA PANDEMI COVID-19 - Ahmad Syarifudin; Fatikhatul Khoiriyah; Hendro Edi Saputro; Adam Malik (Fakultas Hukum, Universitas Samudra, 2021)
This article is an evaluation to campaign rules of regional election 2020 during Pandemic Covid-19 which are many violations of health protocol. Two question will be answered are: 1) how is the legal basis of campaign regional election 2020 during pandemic? 2) how the campaign can be more effective for candidates and save for people during Pandemic Covid-19? Results are: 1) design of campaign method as limited meetings, face to face, and dialog during Pandemic Covid-19 based on article 65 Law No.10 Years 2016 and adopted from “Pedoman Pencegahan dan Pengendalian Coronavirus Disease (Covid-19)” by Minister of health those forbid the crowd and limited social interactions. 2).campaign method as limited meetings, face to face and dialog during pandemic Covid-19 prioritize people save by implement health protocol, give chance to candidate and voters to direct interact, increase the number of campaign participants as limited meetings, face to face, and dialog also allow campaign advertising in mass media and social media.